Hemorrhagic Shock as Complication of Intramural Intestinal Bleeding - Asma Ben Ali; Mohamed Ali Cherif; Walid Mhajba; Hamdi Hamdène Doghri; Malek Hassouna; Youssef Zied El Hechmi; Zouheir Jerbi; Ines Ben Hassen; Mohamed Habib Daghfous (Case Reports in Gastrointestinal Medicine)
Introduction. Mural intestinal hematoma (MIH) is an uncommon complication of anticoagulant therapy. Hemorrhagic shock has been rarely reported as a revealing modality. Results. We report two cases of shock induced by mural intestinal hematoma in patients under oral anticoagulant for aortic prosthetic valve and atrial fibrillation. Patients were admitted to the ICU for gastrointestinal tract bleeding associated with hemodynamic instability. After resuscitation, an abdominal CT scan has confirmed the diagnosis showing an extensive hematoma. Medical treatment was sufficient and there was no need for surgery. Conclusion. Gastrointestinal bleeding associated with shock in patients treated by oral anticoagulant should alert physicians to research a probable MIH. Urgent diagnosis and appropriate medical treatment can avoid surgical interventions.